The Inhibition Effect of Linezolid With Reyanning Mixture on MRSA and its Biofilm is More Significant than That of Linezolid Alone - Zhang, Lulu; Yang, Weifeng; Chu, Yajun; Wen, Bo; Cheng, Yungchi; Mahmood, Tariq; Bao, Mei; Ge, Feng; Li, Li; Yi, Jianfeng; Du, Chengqiang; Lu, Cheng; et al. (Frontiers in Pharmacology, 2022)
Methicillin-resistant Staphylococcus aureus (MRSA) is a superbacterium, and when it forms biofilms, it is difficult to treat even with the first-line of antibiotic linezolid (LNZ). Reyanning mixture (RYN), a compound-based Chinese medicine formula, has been found to have inhibitory effects on biofilms. This study aims to explore the synergistic inhibitory effect and corresponding mechanisms of their (LNZ&RYN) combination on the planktonic as well as biofilm cells of MRSA. Broth microdilution and chessboard methods were employed for the determination of minimum inhibitory concentrations (MICs) and synergistic concentration of LNZ&RYN , respectively. The effect of the combined medication on biofilm and mature biofilm of MRSA were observed by biofilm morphology and permeability experiments, respectively. To unveil the molecular mechanism of action of the synergistic combination of LNZ and RYN, RT-PCR based biofilm-related gene expression analysis and ultra-high pressure liquid chromatography-time-of-flight mass spectrometry based endogenous metabonomic analysis were deployed. The results indicated that 1/16RYN as the best combined dose reduced LNZ (4 μg/mL) to 2 μg/mL. The combined treatment inhibited living MRSA before and after biofilm formation, removed the residual structure of dead bacteria in MRSA biofilms and affected the shape and size of bacteria, resulting in the improvement of biofilm permeability. The mechanism was that biofilm-related genes such as agrC, atlA, and sarA, as well as amino acid uptake associated with the metabolism of 3-dehydrocarnitine, kynurenine, L-leucine, L-lysine and sebacic acid were inhibited. This study provides evidence for the treatment of MRSA and its biofilms with LNZ combined with RYN.